High accuracy differential pressure measurements using fluid-filled catheters – A feasibility study in compliant tubes. Issue 12 (18th September 2015) - Rotman, Oren Moshe; Weiss, Dar; Zaretsky, Uri; Shitzer, Avraham; Einav, Shmuel
Abstract High accuracy differential pressure measurements are required in various biomedical and medical applications, such as in fluid-dynamic test systems, or in the cath-lab. Differential pressure measurements using fluid-filled catheters are relatively inexpensive, yet may be subjected to common mode pressure errors (CMP), which can significantly reduce the measurement accuracy. Recently, a novel correction method for high accuracy differential pressure measurements was presented, and was shown to effectively remove CMP distortions from measurements acquired in rigid tubes. The purpose of the present study was to test the feasibility of this correction method inside compliant tubes, which effectively simulate arteries. Two tubes with varying compliance were tested under dynamic flow and pressure conditions to cover the physiological range of radial distensibility in coronary arteries. A third, compliant model, with a 70% stenosis severity was additionally tested. Differential pressure measurements were acquired over a 3 cm tube length using a fluid-filled double-lumen catheter, and were corrected using the proposed CMP correction method. Validation of the corrected differential pressure signals was performed by comparison to differential pressure recordings taken via a direct connection to the compliant tubes, and by comparison to predicted differential pressure readings of matching fluid–structure interaction (FSI) computational simulations. The results show excellent agreement between the experimentally acquired and computationally determined differential pressure signals. This validates the application of the CMP correction method in compliant tubes of the physiological range for up to intermediate size stenosis severity of 70%.